EvalViz – Surface visualization evaluation wizard for depth and shape perception tasks. (August 2019) - Meuschke, Monique; Smit, Noeska N.; Lichtenberg, Nils; Preim, Bernhard; Lawonn, Kai
Highlights: We extend our tool focusing on the evaluation of depth perception to include the evaluation of shape perception. We extend the generation of task-based experiments based on vascular surface models to arbitrary surfaces models. We provide an automatic preparation of web-based studies to evaluate depth and shape perception in visualization techniques. Graphical abstract: Abstract: User studies are indispensable for visualization application papers in order to assess the value and limitations of the presented approach. Important aspects are how well depth and shape information can be perceived, as coding of these aspects is essential to enable an understandable representation of complex 3D data. In practice, there is usually little time to perform such studies, and the establishment and conduction of user studies can be labour-intensive. In addition, it can be difficult to reach enough participants to obtain expressive results regarding the quality of different visualization techniques. In this paper, we propose a framework that allows visualization researchers to quickly create task-based user studies on depth and shape perception for different surface visualizations and perform the resulting tasks via a web interface. With our approach, the effort for generating user studies is reduced and at the same time the web-based component allows researchers to attract more participants to their study. We demonstrate our framework by applying shape and depth evaluation tasks to visualizations of various surface representations used in many technical and biomedical applications.